2022
DOI: 10.3390/app12031096
|View full text |Cite
|
Sign up to set email alerts
|

Modified Approach Using Mentha arvensis in the Synthesis of ZnO Nanoparticles—Textural, Structural, and Photocatalytic Properties

Abstract: Zinc oxide arouses considerable interest since it has many applications—in microelectronics, environmental decontaminations, biomedicine, photocatalysis, corrosion, etc. The present investigation describes the green synthesis of nanosized ZnO particles using a low-cost, ecologically friendly approach compared to the classical methods, which are aimed at limiting their harmful effects on the environment. In this study, ZnO nanoparticles were prepared using an extract of Mentha arvensis (MA) leaves as a stabiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…The presence of biomolecule-capping agents from the plants was also attributed as the reason for the improved photodegradation of Malachite green using Mentha arvensismediated ZnO NPs reported by Stoyanova et al [81]. A 74% discolouration was reported for M. arvensis-mediated ZnO NPs compared to 45% for bare ZnO NPs under UV irradiation for 120 min.…”
Section: Photodegradation Of Organic Dyes Using Lamiaceae-mediated Zn...mentioning
confidence: 83%
See 1 more Smart Citation
“…The presence of biomolecule-capping agents from the plants was also attributed as the reason for the improved photodegradation of Malachite green using Mentha arvensismediated ZnO NPs reported by Stoyanova et al [81]. A 74% discolouration was reported for M. arvensis-mediated ZnO NPs compared to 45% for bare ZnO NPs under UV irradiation for 120 min.…”
Section: Photodegradation Of Organic Dyes Using Lamiaceae-mediated Zn...mentioning
confidence: 83%
“…The mixture was irradiated in a microwave at 2.45 GHz and 1000 W. A light brown precipitate was obtained and centrifuged at 5000 rounds per minute (rpm) for 8 min. This was followed by cycles of washing the precipitate with ethanol and distilled water and finally drying it in the oven at 60 • C for 24 h. In another study, Stoyanova and associates [81] reported hydrothermally synthesised Mentha arvensis-mediated ZnO NPs. The method involved adding a solution of 0.2 M Zn(CH 3 COO) 2 •2H 2 O and 0.6 M urea at pH 8 to varied extract concentrations of M. arvensis and stirring at 200 rpm.…”
Section: Synthesis Of Lamiaceae-mediated Zno Npsmentioning
confidence: 99%
“…These values correspond to specific lattice planes, denoted by their Miller indices, including (100), (002), (101), (110), (102), (103), (201), (203), and (311) (COD 2300113). The sharp and well-defined nature of these diffraction peaks is indicative of the high crystalline quality of the material [ 38 ]. Notably, there are very small discernible peaks (at 39° and 42°) associated with possible dust contaminants [ 39 , 40 ], indicating synthesis of pure ZnO-NRNs.…”
Section: Resultsmentioning
confidence: 99%
“…Stoyanova et al, reported the green synthesis of nanosized ZnO particles using an extract of Mentha arvensis leaves as a stabilizing/reducing agent, followed by hydrothermal treatment at 180 °C [53]. The obtained ZnO NPs presented photocatalytic activity for the degradation of Malachite Green dye.…”
Section: Phyto-nanotechnologymentioning
confidence: 99%